Subjective assessment by patients of the efficiency of two denture adhesive pastes - (:unkn) unknown (My University, 2005)
Purpose: This study evaluated the subjective responses of 30 denture wearers with regard to the effectiveness of two denture adhesive pastes. Materials and Methods: Thirty patients responded to questions related to retention, chewing ability, taste, duration of adhesives in the mouth, and removal; comparing the use of two denture adhesives based on polymethylvinylether-maleic anhydride compounds or carboxymethyl cellulose. Results: The denture adhesive paste based on polymethylvinylether-maleic anhydride (PVM-MA) compound was rated higher (73% and 87%) than carboxymethyl cellulose (CC) adhesive paste (60% and 37%) on chewing ability and duration in the mouth (p = 0.0001 and p = 0.0001, respectively) by experienced denture wearers in both maxilla and mandible. There were no statistically significant differences between the two denture adhesive pastes on the retention of maxillary dentures, taste, and removal of the adhesive (p = 0.08, p = 0.67, and p = 0.41, respectively). Conclusions: All subjects responded that the retention of their dentures was either a little better or much better when using either of the adhesive pastes. Copyright © 2005 by The American College of Prosthodontists.
Keywords: Denture adhesive; Subjective assessment